Crystallization and preliminary diffraction data of two myotoxins isolated from the venoms of Bothrops asper (Terciopelo) and Bothrops nummifer (jumping viper) - Arni, Raghuvir K. (1993)
Two myotoxins isolated from B. asper (myotoxin II) and B. nummifer (myotoxin I) snake venoms have been crystallized and their diffraction properties are described. These myotoxins are phospholipase A2 variants which lack enzymatic activity; B. asper myotoxin II is a lysine-49 phospholipase. Crystals were obtained at room temperature by standard hanging-drop vapour diffusion methods. Crystals diffracted to a resolution of 2.8 and 2.3 A, respectively.